Indian Texts in Machine Readable form - Havanur, S. K. (Journal of Information and Knowledge, 1984)
The paper discusses the advantages having Indian Language texts in Machine readable form. Suggests the use of Roman letters for transliteration of Indian languages and suggests a scheme for this purpose.